An evaluation of the effective use of computer-based nursing information system in patient care by professional nurses at Dr George Mukhari Hospital - Ntsoele, Motsegoane Monica Naomi (University of Limpopo ( Medunsa Campus), 2011)
An evaluation of the effective use of Computer-based Nursing Information System (CNIS) in patient care by Professional nurses at Dr George Mukhari Hospital. The aim of the study was to evaluate if the CNIS is being used effectively for patient care by professional nurses in different nursing units. The objectives of the study were to describe the perceptions of professional nurses regarding the role of CNIS, to determine the effective use of CNIS, and to identify barriers to the effective use of CNIS in patient care. Quantitative descriptive simple survey research design was used. The setting was at Dr George Mukhari Hospital. The population was all professional nurses who are working on day and night shifts in the wards that have computers installed for the purpose of patient care. Non probability, convenience sample of 120 professional nurses was used. Data was collected utilising a self report questionnaire with 41 closed ended and one open ended questions. Raw data was fed into a SPSS with the assistance of a statistician. Data analysis was conducted through the use of descriptive statistics. The findings are that professional nurses are not using CNIS effectively in patient care. In a unit with a bed occupancy rate of 30-40 patients, and where 30-40 patients are attended to on a daily basis, only 0-2 Nursing Care Plans (NCP) or entries are performed by professional nurses. The majority of professional nurses (56%) never updated NCPs or made an entry before. This is despite the fact that they have indicated positive perceptions with regard to the role of CNIS in patient care. Increased workload, inadequate number of computers, and lack of continuous in-service training were cited by the majority as barriers to the effective use of CNIS in patient care. A problem of increased workload will remain a challenge for as long as available technology is not used appropriately. Hence, hand held devices such as Personal Digital Assistants (PDAs), Electronic Health Records (EHRs) and bedside terminals, are highly recommended. Key concepts: Computer, Nursing, Information, System, Evaluation, Effective, Professional Nurses, Patient care.
Thesis (M Cur)--University of Limpopo, 2011.
Keywords: Computers; Medical records; Computers